Emerging technologies for single-cell glycomics - Sunanda Keisham; Hiroaki Tateno (BBA Advances)
Glycans are present on virtually all cellular surfaces and are important regulators of multicellular communications. Advances in single-cell omics technologies have revolutionized life science research by elucidating cellular heterogeneity through integrated multimodal analyses, providing a comprehensive view of cellular functions. However, dissecting the heterogeneity of glycans at the single-cell level has been challenging due to their structural complexity and unamplifiable nature. Recently, we developed a novel technology called single-cell glycan and RNA sequencing (scGR-seq), which converts glycan information into genetic information using DNA-barcoded lectins, amplifies it by PCR, and simultaneously measures the glycome and transcriptome in thousands of single cells on a next-generation sequencer. In this mini-review, we review the recent advances in single-cell glycomics, focusing on our scGR-seq technology.